Application of Islamic Accounting Principles in Shirkahmudarabah and Musharakah to Realize Justice - Nasim, Arim; Mediawati, Elis; Ningsih, Caria; Heryana, Toni; Nurlaela, Fitri (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to enhance the academic understanding of the application of Islamic accounting principles in the preparation of financial statements as a basis for equitable distribution of profits. The methodology used to guide the research is based on a critical theoretical approach composed of three authorities from Islamic financial institutions consisting of Islamic microfinance institutions, Islamic credit banks, and Islamic commercial banks in Indonesia as informants. The results provide that the profit-sharing method applied still does not appropriate sharia compliance. Findings indicate that Islamic accounting principles are not yet fully included in their accounting principles. In contrast, it shows the accounting principles used are still using capitalist accounting principles. The profit-sharing approach is used by financial institutions because it provides assurance of income for banks. This paper proposes a new perspective about the justice in the profit-sharing method that can be achieved through Islamic accounting principles in shirkah, mudarabah, and musharakah. The results of this study are expected to provide input to the bank in order to apply the principle of actual profit sharing, and then the public can trust in sharia practices in Islamic financial institutions. This is one of the few attempts to suggest the appropriate method of applying Islamic accounting principles relating to justice to create public trust in Islamic financial institutions. It has the promise to strengthen the profit-sharing method, which brings justice to all parties.